2005
DOI: 10.1186/1477-7525-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Combination of qualitative and quantitative methods for developing a new Health Related Quality of Life measure for patients with anogenital warts

Abstract: Background: Anogenital warts are the most easily recognized sign of genital Human Papilloma Virus infection. The objective was to develop a short, valid and reliable questionnaire to measure Health Related Quality of Life (HRQL) in patients with anogenital warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
(13 reference statements)
2
28
0
1
Order By: Relevance
“…Overall, our data coincide with several studies indicating that most men are unaware that GW are caused by HPV infection [13], [30], [32][33]. Although some reports have documented the negative impact of GW on individuals’ quality of life, sexuality and psychological status [12], [16][19], [34][38], few qualitative studies have employed in-depth approaches to understand the experiences of men with GW [12], [15], [18][19], [34], [36], and none have obtained the particular views of South American transgendered women, sex workers or people without GW on this health problem, although a high HPV prevalence has been found in these groups in Argentina, Brazil and Peru [4][5], [39].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our data coincide with several studies indicating that most men are unaware that GW are caused by HPV infection [13], [30], [32][33]. Although some reports have documented the negative impact of GW on individuals’ quality of life, sexuality and psychological status [12], [16][19], [34][38], few qualitative studies have employed in-depth approaches to understand the experiences of men with GW [12], [15], [18][19], [34], [36], and none have obtained the particular views of South American transgendered women, sex workers or people without GW on this health problem, although a high HPV prevalence has been found in these groups in Argentina, Brazil and Peru [4][5], [39].…”
Section: Discussionsupporting
confidence: 90%
“…The results of other studies have suggested that this association can greatly influence the perception of illness; conversely, women may regard cervical dysplasia as stigmatising when they are informed about the sexual transmission of HPV [4,32]. …”
Section: Discussionmentioning
confidence: 99%
“…The prescribed medication was recorded in patients included in the sensitivity group. The CECA questionnaire and the Spanish validated version of the Dermatology Life Quality Index (DLQI) (12,14) were administered at the same time each visit. During the follow-up visit, at 10 ± 3 weeks from baseline for patients in the sensitivity group, and at 15 days from baseline for patients in the reliability group, clinical characteristics were evaluated and the CECA and DLQI questionnaires were again administered, in addition to changes in a single item of self-perceived health status with reference to baseline.…”
Section: Validation and Clinical Use Of The Ceca A Disease-specific mentioning
confidence: 99%
“…The higher the score, the more quality of life is impaired. The DLQI has been translated and validated for use in the Spanish population (12,14).…”
Section: Validation and Clinical Use Of The Ceca A Disease-specific mentioning
confidence: 99%
See 1 more Smart Citation